تحضير مضغوطات قالبية مطولة التأثير للفيراباميل ومقارنتها بالمحضرة بطريقة التلبيس - حماد تميم; ابراهيم لميس (Latakia University Journal -Medical Sciences Series, 2016)
إن هدف هذه الدراسة هو تحضير مضغوطات مطولة التأثير للفيراباميل قالبية وأخرى محضرة بطريقة التلبيس وذلك نظراً لأهمية هذه الأنظمة في إيتاء الأدوية وتحسين مطاوعة المرضى واستجابتهم للعلاج. حضرت عدة صيغ باستخدام بلمرات مختلفة معدلة للتحرر(EURS وEURL) واستخدمت طريقة الضغط المباشر للمضغوطات المعدة للتلبيس,وطريقتا التحثير الرطب والضغط المباشر للمضغوطات القالبية. وتم تقييم الصيغ المحضرة في مرحلة ما قبل الضغط كما درست الخواص الفيزيائية للمضغوطات الناتجة, وأجري فحص الانحلال, ودرست نماذج حركيات التحرر في الزجاج. أظهرت النتائج أن المضغوطات القالبية الحاوية على 7.5أو10% من الإيدراجيت RSوRL على الترتيب, وتلك الملبسة باستخدام محلول التلبيس (15%) المطبق 120في حالة (EuRS100) أو 200مرة في حالة (EURL100) كانت الأفضل حيث حررت حوالي 90-95% من محتواها من الفيراباميل خلال 24 ساعة. The purpose of this study was to prepare prolonged release tablets of verapamil: matrix and coated tablets, because of the importance of these systems in drug delivery and improving the patient compliance and therapeutic efficacy .Different formulations were prepared by using different release-modifiers polymers (EURL100 and EURS100). Direct compression technique was used to prepare coated tablets while matrix tablets were prepared by wet granulation and direct compression methods. The prepared formulations were evaluated in terms of their precompression parameters, physical characteristics, dissolution test and in vitro drug release kinetic studies. The results showed that matrix tablets containing 7.5or10% of EuRS100 and EuRL100 respectively and that coated tablets prepared by using coating solution (15%) which was applied about 120(in case of EuRS100) or 280 (in case of EuRL100) times were the best. These tablets released about 90-95% of verapamil within 24h .